Smart miniaturized wideband/multiband and reconfigurable antenna for modern applications - Boufrioua, Amel (Electronics and telecommunications research., 2018)
"A telecommunications technology is continuously progressing. Its main areas of investigation are, for the most part, motivated by an increasing requirement in terms of data, but are more and more restricted by a hard spectrum of frequencies. Reconfigurable antennas, as well as ultra broadband/multi-band communications systems, have experienced strong development in recent years. New multi-band/wide band antenna concepts have therefore emerged to meet this rising demand. These systems require a low-profile nature and ease of integration with associated electronics. Certainly, the use of such antennas has become extensive in the various modern telecommunications systems. However, the diversity of the characteristics of different bands to be covered (the shape of the radiation patterns, the type of polarization, and the bandwidth required) have increased the difficulty of designing these antennas. The antennas allow for the control of these characteristics for different frequency bands and present a methodology of easy dimensions. Indeed, the miniaturization of the antennas is not without the cause of problems with their performances. The decrease in the size of the antennas is generally accompanied by a degradation of its efficiency and its bandwidth. As a result, designed miniaturized structures usually result from a compromise between bandwidth, efficiency and electrical size. To meet these needs and demands, several techniques will be used in this book to achieve multi-band/wideband performances which deal with the major patch antenna design challenges. In addition, some novel reconfigurable designs for recent applications will be addressed. The authors hope that this book will provide a full analysis and will present new research in this active field. This book will be divided into six chapters"--